Navajo sovereignty : understandings and visions of the Dine people - Denetdale, Jennifer; Lee, Lloyd L., 1971- (Critical issues in indigenous studies., 2017)
"A call for the rethinking Navajo sovereignty in a way more rooted in Navajo beliefs, culture, and values"--Provided by publisher.